СURRENT TRENDS IN THE DIAGNOSIS OF INJURIES MAXILLOFACIAL REGION - Babkina, T.M.; Demidova О.О. (World of Medicine and Biology, 2013)
Diagnostic studies performed by cone beam tomograph PAX-ZENITH 3D made it possible to receive high resolution images of hard tissues and to detect the localization of bone tissue defects and fractures. High resolution ability and three-dimensional tomographic image reconstructions of high quality allowed to determine optimally and in short terms the scope and method of operation treatment, to choose good scheme of conservative treatment. Examinations performed in dynamics helped to estimate cosmetic and functional results of corrective and decorative surgery, contributed to prevention of complications, and helped to define the effectiveness of conservative therapy. The obtained data helped to determine the peculiarities of application of cone beam tomography in the diagnostics of maxillofacial injuries, to identify the specific defects where the cone beam tomography is the most informative, to discover weak and strong sides, to offer modern algorithms of x-ray diagnostics for maxillofacial surgeons.